THE INFLUENCE OF THE QUALITY OF HUMAN RESOURCES ON THE ABSORPTION RATE OF THE BUDGET AT THE BOGOR DISTRICT FISHERIES AND LIVESTOCK SERVICE OFFICE - Mursyidah, Euis; Rahmawati, Rita; Soebagdja, R. Oetje (Universitas Djuanda, 2021)
Organizations are required to have both adequate human resources and budget, in order to realize programs and activities so that the established budget planning can be absorbed. The problem is, there are still many governmental organizations which are unable to optimize budget absorption. This study aims to test the influence of budget planning and human resource quality on budget absorption in fisheries and livestock offices of Bogor Regency. The variables used in this study were budget planning and human resource quality as the independent variables and the budget absorption as the dependent variable. The author used an associative quantitative method as the method in this study. The data collection technique used was primary data which was directly obtained from the object of the study by disseminating questionnaires. The population in this study is all employees of the fisheries and livestock office of Bogor Regency. A random sampling technique was used in this study. The Slovin Formula was used to determine the number of samples which were taken from a certain modified population. There were 54 respondents in this study. Multiple regression analysis was used in this study.